Competing for Loyalty: The Dynamics of Rallying Support - Iaryczower, Matias; Oliveros, Santiago (American Economic Review, 2017)
We consider a class of dynamic collective action problems in which either a single principal or two competing principals vie for the support of members of a group. We focus on the dynamic problem that emerges when agents negotiate and commit their support to principals sequentially. We show that competition reduces agents' welfare with public goods, or if and only if there are positive externalities on uncommitted agents, and increases agents' welfare with public bads. We apply the model to the study of corporate takeovers, vote buying, and exclusive deals. (JEL D42, D62, D72, D82, G34, H41)